Impact of Economic Policy Uncertainty on Capital Structure : Evidence from United Kingdom - LI, Xiao (2020)
This study is researching how economic policy uncertainty impact on the capital structure for UK listed companies between 2012 and 2019. It shows that uncertainty of economic policy has a negative effect on leverage ratio. That is, as economic policy uncertainty increases, the firm's leverage ratio will fall. In addition, this paper is analyzed capital structure from investment, cash holding and cost of debt; these three aspects are affected by policy uncertainty. Specifically, in the case of uncertainty, the firm will become more cautious in investment decisions and hold more cash to maintain stable operations; the increase in uncertainty will add the firm’s cost of debt, which will lead to a larger scale of company debt financing and make the capital structure decision become more conservative. Additionally, this study provides empirical analysis with control variables, including firm size, asset structure, profitability and effective tax. The results of firm size and asset structure have positive correlation, while profitability, current ratio and effective tax have negative relationship with economic policy uncertainty. These results are consistent with previous studies. Furthermore, this study carries out robustness test, modifies the endogenous problem and make the result more reliable.